The Application Of E-MTBS To Increase The Quality Of Midwife Service In Giving Midwifery Care For Under Five Years Old Toddler - Muhasshanah Muhasshanah; Neny Yuli Susanti (Universitas STRADA Indonesia, 2020)
MTBS is one of the government’s efforts to reduce infant mortality rate. Most of sick toddler cases found in Situbondo regency are dealing with dengue fever and pneumonia, especially in Banyuputih Public Health Center area. One of the approaches to reduce the infant mortality rate is to consistently fill the MTBS format. However, due to limited manpower and the workload, medical personnel especially midwife could not optimally fill out the MTBS, so that toddler diseases could not be detected early. It is because the filling format and the reporting system of MTBS are not user friendly. The objective of this research is to develop MTBS implementation by using Information Technology System, in order to increase the quality of midwife service in giving midwifery care and reduce the infant mortality rate in Banyuputih Public Health Center area. This research generated a product in the form of information system called e-MTBS